2011
DOI: 10.1310/hpj4605-336
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Risk Factors and Therapeutic Outcomes for Clostridium difficile Infection

Abstract: Purpose: To determine the Clostridium difficile infection (CDI) recurrence rate at the Veterans Affairs Medical Center (VAMC) in Fargo, North Dakota, and to determine whether certain variables (eg, type of antibiotic, medication, chronic disease state, CDI symptom control) were predictive of CDI recurrence. Methods: Demographic information and laboratory data from 174 adult outpatients and inpatients were collected from electronic medical records between January 1997 and September 2009. In addition, informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Table 1 shows the main characteristics of the included studies. The majority of the studies were conducted in North America (n = 26) [13,14,[16][17][18][19][20]23,[25][26][27]31,33,34,38,40,41,[43][44][45][46][47][48][49][50][51], whilst 7 were conducted in Europe (mainly in the UK) [21,22,[28][29][30]32,35]. One more study included patients from North America and the UK [15], four from Asia (South Korea and Taiwan) [36,37,39,42] and one from Argentina [24].…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 shows the main characteristics of the included studies. The majority of the studies were conducted in North America (n = 26) [13,14,[16][17][18][19][20]23,[25][26][27]31,33,34,38,40,41,[43][44][45][46][47][48][49][50][51], whilst 7 were conducted in Europe (mainly in the UK) [21,22,[28][29][30]32,35]. One more study included patients from North America and the UK [15], four from Asia (South Korea and Taiwan) [36,37,39,42] and one from Argentina [24].…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Six studies were funded by pharmaceutical companies [14][15][16][17][18]21], 18 received grants from non-profit organisations and institutions or universities [13,19,22,24,25,27,30,33,34,36,40-45, 49,51] and 4 received funds from both [20,23,28,38]; no data were available for the remaining 11 studies [26,29,31,32,35,37,39,[46][47][48]50]. In 5 of the 18 non-profit-funded studies the authors reported having received grants from pharmaceutical companies [19,25,27,34,49], as did 1 of the 11 studies for which no funding was reported [31].…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations